Fatores associados à prevalência da coinfecção HIVsífilis em pessoas no início da terapia antirretroviral em Belo Horizonte - MG - Luana Andrade Simões (2021)
Sexually transmitted infections (STIs) are considered to be one of the biggest public health problems worldwide. Among them, syphilis and HIV, which have a transmission route, diagnosis, age group and similar population groups, stand out. Infection with Treponema pallidum can alter the viral load and the number of TCD4 + lymphocytes, resulting in a greater condition of morbidity and mortality in people with HIV. HIV and syphilis are of special interest to managers and public health professionals, have specific bulletins for epidemiological surveillance and are mandatory to report. The objective in conducting the study was to evaluate the factors associated with the prevalence of HIV / syphilis coinfection in people at the beginning of antiretroviral therapy in the city of Belo Horizonte, Minas Gerais. This is a cross-sectional study, part of a cohort entitled Project ECOART, conducted in three public services of reference in specialized care for HIV / AIDS in Belo Horizonte. The eligibility criteria were: individuals starting antiretroviral therapy (ART); age ≥ 16 years; being followed up in one of the three reference services and who agreed and signed the Informed Consent and Assent Form. Sociodemographic, behavioral, clinical data related to pharmacological treatment and the service were obtained from baseline interviews, medical records and the Drug and Examination Control System. HIV / syphilis coinfection was present in 10.6% of the individuals and among the registered STIs, syphilis was predominant. It was observed that 81.5% of the individuals were male, with a mean age of 34.7 years (SD = 10.9); predominance of the 20- to 34-year-old age group (53.4%); 79.7% were single, divorced or widowed; 48.9% declared themselves brown and 38.9% had 10 to 12 years of schooling. In the multivariate logistic regression analysis, the factors associated with the prevalence of HIV / syphilis co-infection were, the use of alcohol; the diagnosis of other STIs; treatment with ART in days and antiretroviral regimen containing Dolutegravir. Knowledge about the factors associated with the prevalence of HIV / syphilis co-infection can support decision-making by professionals involved in care, leading to safe sexual practices for the prevention of syphilis in people with HIV.